2015
DOI: 10.3109/00365521.2015.1036113
|View full text |Cite
|
Sign up to set email alerts
|

Alternative sedation for the higher risk endoscopy: a randomized controlled trial of ketamine use in endoscopic retrograde cholangiopancreatography

Abstract: In this pilot study, sedation for endoscopy with ketamine and midazolam was as effective as conventional sedation, as acceptable to patients, and was not associated with dysphoric events. Ketamine may have potential as an agent for sedation in higher risk patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 29 publications
0
3
0
1
Order By: Relevance
“…Ketamine is an analgesic that is most effective when used alongside a low-dose opioid; while it does have analgesic effects by itself, the doses required for adequate pain relief when it is used as the sole analgesic agent are considerably higher and far more likely to produce disorienting side effects. 16 – 19 In our study, we found that the incidence of adverse reactions were greatly increased in those injected with 1 mg/kg ketamine before anesthesia induction than those injected with butorphanol ( P <0.05). In addition, injection with ketamine combined with butorphanol before anesthesia could efficiently shorten recovery time and reduce incidence of adverse reactions than application of each drug separately.…”
Section: Discussionmentioning
confidence: 59%
“…Ketamine is an analgesic that is most effective when used alongside a low-dose opioid; while it does have analgesic effects by itself, the doses required for adequate pain relief when it is used as the sole analgesic agent are considerably higher and far more likely to produce disorienting side effects. 16 – 19 In our study, we found that the incidence of adverse reactions were greatly increased in those injected with 1 mg/kg ketamine before anesthesia induction than those injected with butorphanol ( P <0.05). In addition, injection with ketamine combined with butorphanol before anesthesia could efficiently shorten recovery time and reduce incidence of adverse reactions than application of each drug separately.…”
Section: Discussionmentioning
confidence: 59%
“…This may be related to the use of higher doses of ketamine and it is dissociative effects. In a randomized controlled trial by Narayanan et al ., 28 ketamine was not found to cause emergence symptoms. In our study, the mean ketamine dose in younger patients (62 ± 23.4 mg) was more than twice the median dose (25 mg [25–37.5]) used in the study by Narayanan et al .…”
Section: Discussionmentioning
confidence: 92%
“… 10 - 12 Epidural and intravenous administration of ketamine has been shown to reduce postoperative analgesic requirements by 35-40%. 13 - 16 Adding propofol to ketamine reduces the incidence of dose-dependent adverse effects on the cardiovascular and respiratory systems. 10 , 11 …”
Section: Discussionmentioning
confidence: 99%